Peripheral visual field loss and activities of daily living. Issue 1 (21st February 2023) - Okrent Smolar, Avital Lily; Gagrani, Meghal; Ghate, Deepta
Abstract : Purpose of review: Peripheral visual field (VF) loss affects 13% of the population over 65. Its effect on activities of daily living and higher order visual processing is as important as it is inadequately understood. The purpose of this review is to summarize available literature on the impact of peripheral vision loss on driving, reading, face recognition, scene recognition and scene navigation. Recent findings: In this review, glaucoma and retrochiasmal cortical damage are utilized as examples of peripheral field loss which typically spare central vision and have patterns respecting the horizontal and vertical meridians, respectively. In both glaucoma and retrochiasmal damage, peripheral field loss causes driving difficulty – especially with lane maintenance – leading to driving cessation, loss of independence, and depression. Likewise, peripheral field loss can lead to slower reading speeds and decreased enjoyment from reading, and anxiety. In glaucoma and retrochiasmal field loss, face processing is impaired which impacts social functioning. Finally, scene recognition and navigation are also adversely affected, impacting wayfinding and hazard detection leading to decreased independence as well as more frequent injury. Summary: Peripheral VF loss is an under-recognized cause of patient distress and disability. All peripheral field loss is not the same, differential patterns of loss affect parameters of activities of daily living (ADL) and visual processing in particular ways. Future research should aim to further characterize patterns of deranged ADL and visual processing, their correlation with types of field loss, and associated mechanisms.